Stroke and stroke rehabilitation : a description of the results of cerebrovascular disease and the proposal of realistic goals for rehabilitation - Watson, Ruth Marguerite (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D.) -- University of Stellenbosch, 1989.